Gender Based Violence Reporting System: A Case Study Kabale University Police Station. - Mbaine, Abert (Kabale University, 2024)
The status of women in society is very diverse worldwide. Among many important traits associated with the differentiation of gender inequality is religion, which itself must be regarded as a fluid concept with interpretations and practices 'embedded' and thus varying concerning cultural and historical relations. Three categories of states have emerged from the analysis: states where the majority of inhabitants are without religious affiliation, which display the lowest levels of gender inequality; Christian and Buddhist societies, with average levels of gender inequality; and states with the highest levels of gender inequality across the observed variables, whose inhabitants adhere to Islam and Hinduism. Gender inequalities can be defined as culturally and socially created differences between men and women when both sexes do not have the same share in the decision-making and wealth of a society (Ridgeway, 2004). 2 We understand religion as an ideology that affects the socio-political practices of a society and as a complex cultural system of meanings, symbols, and behaviors in communities (Stump, 2008)